Pengembangan Front-End dan Pengambilan Data untuk Visualisasi Data dan Aktivitas Pramuka Kota Mataram - Budisantoso, Arvelio Renathan; Irmawati, Budi; Afwani, Royana (Journal of Computer Science and Informatics Engineering (J-Cosine), 2025)
Mataram City's scouting administration information system currently relies on manual processing like Google Forms and Excel that encounter challenges at the Scout Unit level up to the District Council. These manual processing result in data mistakes, reporting delays, and challenges for the Regency Council to obtain real-time information. This project aims to create a website-based information system using the Scrum methodology in order to centrally digitalize members, scoutmasters, and scout activities data management. Using Next.js and TypeScript, the authors develop a front-end and data retrieval from API Endpoints. This application to enhance user productivity, facilitate cross-level reporting, and provide effective data visualization. These benefits are supported by the User Acceptance Testing results, which show an average feasibility score of 81.74% in the "good" category across functionality, reliability, usability, and efficiency aspects. This confirms that the digitalization of scout administration is both ready to be implemented and aligned with user expectations.